2016
DOI: 10.1097/md.0000000000004351
|View full text |Cite
|
Sign up to set email alerts
|

Role of altered esophageal intraluminal baseline impedance levels in patients with gatroesophageal reflux disease refractory to proton pump inhibitors

Abstract: Numerous studies have investigated utility of esophageal intraluminal baseline impedance levels (BILs) in gastroesophageal reflux disease (GERD). However, effect of BILs in refractory GERD (RGERD) has not been well investigated. The aim of this study is to evaluate role of BILs in RGERD patients. Total 62 subjects with refractory gastroesophageal reflux symptoms underwent 24-hour impedance-pH monitoring and gastroendoscopy. Distal BILs in acid reflux type were significantly lower than those in nonacid reflux t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…32 Besides, it showed that MNBI was negatively correlated to acid-related parameters, such as episodes of acid reflux, DeMeester score, and AET. 33 Based on our results, patients with AET 4-6% and AET > 6% both had lower MNBI than patients with AET <4%. ROC curve analysis revealed MNBI had an advantage in diagnosing GERD with high sensitivity and specificity, so MNBI is crucial for GERD diagnosis in suspected patients with AET 4-6%.…”
Section: Despite the Limitations Of Currently Available Esophageal Te...supporting
confidence: 50%
See 1 more Smart Citation
“…32 Besides, it showed that MNBI was negatively correlated to acid-related parameters, such as episodes of acid reflux, DeMeester score, and AET. 33 Based on our results, patients with AET 4-6% and AET > 6% both had lower MNBI than patients with AET <4%. ROC curve analysis revealed MNBI had an advantage in diagnosing GERD with high sensitivity and specificity, so MNBI is crucial for GERD diagnosis in suspected patients with AET 4-6%.…”
Section: Despite the Limitations Of Currently Available Esophageal Te...supporting
confidence: 50%
“… 32 Besides, it showed that MNBI was negatively correlated to acid-related parameters, such as episodes of acid reflux, DeMeester score, and AET. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded if they were found to have a tumor, peptic ulcer, or any mucosal abnormality other than esophagitis and superficial gastritis on endoscopy; a history of gastrointestinal surgery; severe organ dysfunction; or primary or secondary severe esophageal motility disorders (eg, achalasia, nutcracker esophagus, scleroderma, and diabetes mellitus). [ 12 ] The study protocol was approved by the ethics committee of the First Affiliated Hospital of Nanjing Medical University. All patients provided informed consent before the start of the investigation.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, they confirmed that BI level is lowest in ERD and that BI levels were low in both ERD and NERD, as previously reported. [4][5][6][7][8][9]12 In particular, in a comparison with the control group, the authors showed cut-off values for sensitivity and specificity of 55.4% and 100%, respectively, based on 1764 ohm.…”
mentioning
confidence: 99%
“…[4][5][6] Therefore, esophageal BI is used to predict the therapeutic effect of PPI related to severity of acid exposure. [6][7][8] However, there is still insufficient evidence to standardize this strategy.…”
mentioning
confidence: 99%